Comparative study of the effects on the EEG of drinking monotherapy with Naftussya water and therapy supplemented with "Myroslava" and "Khrystyna" mineral waters - Myroslava Hrytsak; Dariya Popovych; Nataliya Badiuk; Ivanna Hrytsan; Xawery Zukow (Kazimierz Wielki University, 2022)
Background. Earlier we showed that the newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets' spa have favorable effects on metabolism and neuroendocrine-immune complex of patients with their dysfunction. This report analyzes the effect of balneotherapy on the parameters of the electroencephalogram of the same contingent of patients. Materials and Methods. The object of clinical-physiological observation were 34 men aged 23-70 years, who underwent rehabilitation treatment of chronic cholecystitis and pyelonephritis in remission in the Truskavets' spa. The examination was performed twice, before and after a 7-10-day course of balneotherapy. All patients received bioactive water Naftussya, however, 11 men additionally drank water "Khrystyna", and the other 11 men - water "Myroslava". The subject of the study were the parameters of the electroencephalogram. Results. The complex balneotherapy by interval use of sulfate-chloride sodium-magnesium mineral waters with Naftussya water causes significant changes in the constellation of EEG parameters, which are different from the effects of Naftussya water monotherapy. Own effects of mineral waters are estimated by modeling. Two patterns of neurotropic effects have been identified - activating and inhibitory. In general, the neuromodulating effects are physiologically favorable. Conclusion. The newly created sulfate-chloride sodium-magnesium drinking mineral waters of Truskavets' spa have favorable neuromodulating effects on patients with chronic cholecystitis and pyelonephritis.